2017
DOI: 10.1007/s00784-017-2047-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based versus conventional cytology of oral brush biopsies: a split-sample pilot study

Abstract: LBC facilitates the cell collection due to simpler handling and less transfer errors by dentists and may improve the overall diagnostic accuracy of oral brush biopsies in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…45 Of note, 7 studies processed oral brush biopsy samples using LBC, 5 of which reported sensitivity and specificity. 10,21,27,44,45 Navone et al 21 showed sensitivity and specificity of 95.1% and 99% in 1 study, and 86.5% and 94.3% in another. 27 The methodological assessments of the included studies in this review are presented in Table 3.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…45 Of note, 7 studies processed oral brush biopsy samples using LBC, 5 of which reported sensitivity and specificity. 10,21,27,44,45 Navone et al 21 showed sensitivity and specificity of 95.1% and 99% in 1 study, and 86.5% and 94.3% in another. 27 The methodological assessments of the included studies in this review are presented in Table 3.…”
Section: Discussionmentioning
confidence: 91%
“…In the context of brush type used, the cytobrush has been utilized in 19 studies. Of these, twelve studies showed sensitivity and specificity of 94.6% and 99.5%, 85.7% and 95.9% using conventional exfoliative cytology and 95.1% and 99.0% using liquid‐based cytology in the same study, 100% and 97.4% using a combination of cytological and DNA‐image cytometry assessment, 79% and 100%, 78% and 96%, 86.5% and 94.3%, 92.3% and 51.7%, 69% and 100%, 70.3% and 77.9%, 84.4% and 88.9%, 100% and 64%,, 96.3% and 90.6% using conventional exfoliative cytology, and 97.5% and 68.7% using liquid‐based cytology in the same study, respectively. The sensitivity and specificity of 7 studies were not reported .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations